Influence of oral health behavior and sociodemographic factors on remaining teeth in Korean adults: 2010–2012 Korea national health and nutrition examination survey. Issue 48 (November 2016) - Song, In-Seok; Han, Kyungdo; Choi, Yeon-Jo; Ryu, Jae-Jun; Park, Jun-Beom
Abstract : Abstract: In this study, the number and location of remaining teeth were analyzed according to sociodemographic variables, anthropometric measurements, and oral health behavior patterns. The hypothesis was that the number and location of remaining teeth would be affected by oral health behavior and by sociodemographic factors, such as education levels, household income, and urban/rural residency. This nationwide cross-sectional study was performed with a total of 36, 026 representative Korean adults aged 19 and older. The data were taken from the 2012–2012 Korea National Health and Nutrition Examination Survey. Men had, on average, significantly more remaining teeth than women did. Women brushed their teeth more often than men per day and were more likely to brush their teeth after meals. The participants with higher education levels or household income had significantly more remaining teeth; the number of daily tooth brushing was positively associated with the number of remaining teeth; urban residents had significantly more remaining teeth than rural residents; and elderly adults had fewer remaining teeth than younger adults had (all with P < 0.05). The participants were more likely to retain their incisors (especially their canines) for their entire lifetimes than do so for their molars. From the incisors to the second premolars, they had more mandibular teeth than maxillary teeth, but among molars, they had more maxillary teeth than mandibular teeth. Elementary graduates with low household income had fewer remaining teeth than did university graduates with high household income ( P < 0.0001). Finally, participants with high socioeconomic status were more likely to lose their molar teeth than anterior teeth compared to those with low socioeconomic status. The participants who brushed their teeth fewer times per day, those with low household incomes and/or education levels, and those who lived in rural districts had significantly higher prevalence of tooth loss than did other groups in Korean adults. Participants had more anterior and premolar teeth on mandible, but they had more molars on maxilla. In addition, participants with high socioeconomic status were more likely to lose their molar teeth than anterior teeth compared to those with low socioeconomic status.